RESEARCH ON EXCAVATION RESISTANCE FUNCTION OF AUTOMATIC EXCAVATOR (MT) - CAI GanWei; WANG Fen; TIAN JunWei; QI Gang (Jixie qiangdu)
The research on the excavation resistance function of excavator is the key step to realize automatic excavation. Based on the classical soil-bucket model, a digging resistance model of automatic excavator is proposed. The expression of the excavation resistance function for the whole automatic excavation process of three stages of penetration, cutting and loading and the detailed calculation process of its coefficients are given. The existing bucket shape model is modified to make it more in line with the actual shape. Taking a certain excavation track and silty clay as examples, the theoretical excavation resistance curve under this working condition is calculated and compared with the results obtained by Ls-Prepost software simulation. The shape of the two curves is similar, and the maximum error is less than 10.2%, the results show that the resistance model can be used as the excitation function of excavator dynamic performance analysis. It has a good reference value to the dynamic performance research of automatic excavator.